Perlocutionary Speech Act of Conveying Bad News in Medical Communication - Sejati, Amanda Puspanditaning; Ningrum, Dedah; Ridwan, Heri; Handayani, Sifa Rini (Journal of Language and Literature, 2024)
Conveying bad news in the medical field, can present a challenging scenario as it tends to evoke emotional responses such as sadness, anxiety, and anger in the recipients. Essentially, this communication scenario holds the potential to impact the recipient, aligning with the concept of perlocutionary speech acts. Research into perlocutionary speech acts in the context of delivering adverse news within medical communication has not been extensively explored. This study aims to provide an overview of perlocutionary speech acts observed in delivering bad news within a medical context, as depicted in The Resident series. Employing a qualitative research design, this study applied a pragmatic approach for data analysis. The dataset for this study comprises the dialogues of doctors in 11 distinct contexts involving the communication of bad news in The Resident series. The results of the study showed that perlocutionary speech acts appeared in the context of delivering bad news, including the act of asking for confirmation, calming, explaining, informing, suggesting, and convincing. Additionally, these speech acts incite various emotional responses in the recipients, including sadness, anger, self-blame, panic, surprise, and calm. The outcomes of this research serve as a valuable reference for enhancing communication skills and pragmatic competence among healthcare professionals when confronted with the task of conveying bad news.